"O Brasil não é só doença": o programa de saúde pública de Juscelino Kubitschek "Brazil isn't only disease": Juscelino Kubitschek's public health program - Gilberto Hochman (História, Ciências, Saúde: Manguinhos)
Analisa o programa de saúde do candidato à Presidência da República Juscelino Kubitschek e seu diálogo com interpretações que identificavam o Brasil como 'país doente' a ser recuperado pela medicina. Os contextos nacional e internacional são marcados pela ideia de desenvolvimento e pelo otimismo sanitário do pós-Segunda Guerra Mundial. Aborda o modo como Kubitschek elaborou, no contexto de seu projeto de desenvolvimento, os temas da centralidade das endemias rurais e do abandono do trabalhador rural, caros ao movimento sanitarista da década de 1910, e indica a articulação de saúde e desenvolvimento nesse programa setorial, bem como a introdução de agendas sanitárias emergentes. Analyzes the public health program that Juscelino Kubitschek presented while running for president and its dialogue with interpretations that identified Brazil as an ailing country that should be recovered through public medicine. The proposals and goals contained in Kubitschek's healthcare program, as released during his 1955 campaign, serve as the main sources for this analysis. They also were key to establishing this dialogue, which was both prompted and shaped by a national and international context characterized by the post-war idea of development and public health optimism. Within the context of his development project, the article looks at how Kubitschek elaborated the themes of the centrality of rural endemic disease and the abandonment of the rural worker, both dear to the sanitary movement in the 1910s. It also underscores how Kubitschek the candidate endeavored to link health and development within this arena of government policy.